2016
DOI: 10.1038/ajg.2016.344
|View full text |Cite
|
Sign up to set email alerts
|

The Periscreen Strip Is Highly Efficient for the Exclusion of Spontaneous Bacterial Peritonitis in Cirrhotic Outpatients

Abstract: The Periscreen strip is a rapid and highly efficient tool for excluding SBP in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…Esophageal bleeding was determined using a fiberoptic panendoscope. Spontaneous bacterial peritonitis was defined as an ascitic fluid infection without an evident intra-abdominal surgically treatable source 40 and was diagnosed according to the clinical manifestations and ascitic fluid findings as described previously 41 . Severe acute exacerbation of chronic hepatitis B was defined as an abrupt ALT elevation >5 × the upper limit of the normal range associated with jaundice and a prolonged prothrombin time in patients with chronic hepatitis B 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Esophageal bleeding was determined using a fiberoptic panendoscope. Spontaneous bacterial peritonitis was defined as an ascitic fluid infection without an evident intra-abdominal surgically treatable source 40 and was diagnosed according to the clinical manifestations and ascitic fluid findings as described previously 41 . Severe acute exacerbation of chronic hepatitis B was defined as an abrupt ALT elevation >5 × the upper limit of the normal range associated with jaundice and a prolonged prothrombin time in patients with chronic hepatitis B 42 .…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of SBP in asymptomatic outpatients was less than 1.5% in a large series [12], while it was greater than 8% in the symptomatic outpatients. On the contrary, in the series by Thevenot et al on the usefulness of Periscreen TM® strip [11], the prevalence of SBP in outpatients was significantly lower than that in the inpatients (2.1% vs. 11.2%; p < 0.001). Differences in the SBP prevalence between inpatients and outpatients were elucidated in a study conducted by Cadranel et al [9], who reported that in the inpatients, the cause of cirrhosis was more frequently alcoholrelated, the Child-Pugh score was higher and more often C than B, the platelet count was lower, and the serum total bilirubin concentration was higher.…”
Section: Discussionmentioning
confidence: 76%
“…A double-blind search of studies published in Medline until July, 2019 on the topic of prevalence and the associated factors of spontaneous bacterial peritonitis in asymptomatic outpatients having therapeutic paracenteses was performed using the following keywords: ascites, spontaneous bacterial peritonitis, outpatient procedures, asymptomatic patients, cirrhosis, and urinary reagent strips. Six studies, including those conducted on cirrhotic outpatients, have been published as full papers on this topic [5][6][7][8][9]11]. One of these studies was an ancillary study [9] of the multicenter study that aimed at evaluating the reagent strip Multistix as a diagnostic tool for SBP [12].…”
Section: Literature Analysismentioning
confidence: 99%
See 2 more Smart Citations